Reflexiones sobre la importancia de la celebración de la 15ª reunión ENOTHE en España, A Coruña en 2009 = Reflections on the importance of celebrating the 15th ENOTHE meeting in Spain, A Coruña, in 2009 - van Bruggen, Hanneke (Asociación Profesional Gallega de Terapeutas Ocupacionales (APGTO), 2008)
SUMMARY In this paper the European policies with respect to higher education and social affairs will be discussed in relation with the development of occupational therapy in Europe and in particularly Spain.Due to the quite drastic changes in the social reality in Europe based on demographic trends, it is expected that occupational therapy will play a bigger role in the social arena and in health prevention and promotion.2009 will be the European year of linking education, culture and creativity. A better theme for occupational therapist could hardly be found. We expect to find Galician culture and creativity linked to European occupational therapy education in la Coruna. RESUMENEn este informe se hablará de las políticas europeas en lo que conciernen a la enseñanza superior y asuntos sociales en relación con el desarrollo de la terapia ocupacional en Europa y en particular en España.Debido a los cambios bastante drásticos de la realidad social en Europa basada en tendencias demográficas, se espera que la terapia ocupacional juegue un papel más grande en la arena social y en la prevención y la promoción de la salud.2009 será el año europeo de unir la educación, la cultura y la creatividad. Sería difícil encontrar un mejor tema para el terapeuta ocupacional.Esperamos encontrar en A Coruña, un vinculo entre la cultura y creatividad gallega y la educación de la Terapia Ocupacional a nivel europeo.